AB0281 Characterization of changes in lymphocyte subsets in baricitinib-treated patients with early, dmard naÏve, rheumatoid arthritis in a phase 3 study. (15th June 2017) - Takeuchi, T; Fleischmann, R; Schiff, M; Issa, M; Macias, W; Rooney, T; Zuckerman, S; Schlichting, D; McInnes, I
Abstract : Background: In RA-BEGIN (NCT01711359 ), baricitinib (bari), an oral Janus Kinase (JAK)1/JAK2 inhibitor, improved signs and symptoms of moderately to severely active RA in patients (pts) who had received no or limited prior csDMARD and no prior bDMARD therapy. 1 Objectives: To analyse changes in absolute lymphocyte count (ALC) and cell subsets (LCS) in RA-BEGIN. Methods: Pts (N=588) were randomised 4:3:4 (MTX up to 20mg QW, bari 4mg QD, bari 4mg+MTX) for 52 Wks. T and B cells plus subsets and natural killer (NK) cells were quantified by flow cytometry at baseline (BL) and Wks 4, 12, and 32. Results: At BL, low cell counts were observed in 4.3%, 8.2%, 5.3%, 18.3%, and 19.7% of pts for ALC, CD3+, CD8+, B (CD19+), and NK cells. In the MTX group, slight declines in mean counts were observed for all cell types at post-BL visits (Table). For bari and bari+MTX, cell counts increased for all cell types at Wks 4 and 12, with, except for B cells, a return towards BL, or slightly below, at Wk 32. Changes in other T and B cell subsets generally reflected these patterns (data not shown). Treatment emergent (TE) low NK cell counts occurred in 11.6%, 13.4%, and 20.5% of pts for MTX, bari, and bari+MTX; TE low CD8+ cell counts occurred in 5.2%, 3.2%, and 8.3% of pts. Overall serious infection (SI) rates were 3.8%, 3.8%, and 2.3% for all pts in MTX, bari, and bari+MTX; rates were 6.8% (4 of 59 pts), 4.8% (2 of 42), and 2.8% (2 of 72) for pts with ≥1 low post-BL NK cell count and 15.8% (3 of 19), 25.0% (2 of 8), and 5.3% (1 of 19) for pts with ≥1 low post-BL CD8+ cell count. Herpes zoster (HZ) rates were 1.0% 2.5%, and 2.3% for all pts in MTX, bari, and bari+MTX; rates were 3.4% (2 of 59 pts), 4.8% (2 of 42), and 4.2% (3 of 72) for pts with ≥1 low post-BL NK cell count and 10.5% (2 of 19), 12.5% (1 of 8), and 5.3% (1 of 19) for pts with ≥1 low post-BL CD8+ cell count. Conclusions: Low B and NK cell counts were common at BL, and post-BL changes within normality occurred in all treatment groups. Compared to MTX, bari was not associated with an increase in the % of pts with low NK or CD8+ cell counts while bari+MTX did show an increase in the % of pts with a low NK cell count. Changes appear distinct for LCS suggesting different mechanisms may underscore the effect of JAK inhibition. Whether low NK or CD8+ cell counts predispose to increased risk for SI or HZ was difficult to assess due to few pts with low counts experiencing these events. References: Fleischmann R, et al. A & R. 2016. Disclosure of Interest: T. Takeuchi Consultant for: Pfizer Japan, Astra Zeneca KK, Eli Lilly Japan KK, Novartis Pharma KK, Daiichi Sankyo Ltd, Nipponkayaku Ltd, Janssen Pharma KK, Merck Serono Ltd, Takeda Pharma Ltd, Mitsubishi Tanabe Pharma, Astellas Pharma, Abbvie GK, Bristol-Myers KK, Asahi Kasei Medical KK, Speakers bureau: Celtrion, Nipponkayaku Ltd, Pfizer Japan, UCB Japan, Daiichi Sankyo Ltd, Takeda Pharma Ltd, Chugai Pharma Ltd, Abbvie GK, Bristol-Myers KK, Eisai Co Ltd, Mitsubishi Tanabe Pharma, Janssen Pharmac KK, Astellas Pharma, R. Fleischmann Grant/research support from: Abbvie, Amgen, AstraZeneca, Bristol-Myers Squibb, Celgene, Eli Lilly and Company, Genetech, GSK, Janssen, Pfizer, Merck, Regeneron, Roche, Sanofi-Aventis, UCB, Consultant for: Abbvie, Akros, Amgen, Bristol-Myers Squibb, Celgene, Eli Lilly and Company, Genentech, GSK, Janssen, Pfizer, Sanofi-Aventis, UCB, M. Schiff Consultant for: Abbvie, BMS, Eli Lilly and Company, Johnson & Johnson, Speakers bureau: Abbvie, M. Issa Employee of: Eli Lilly and Company, W. Macias Employee of: Eli Lilly and Company, T. Rooney Employee of: Eli Lilly and Company, S. Zuckerman Employee of: Eli Lilly and Company, D. Schlichting Employee of: Eli Lilly and Company, I. McInnes Grant/research support from: Eli Lilly and Company, Abbvie, Pfizer, Novartis, Roche, Janssen, Consultant for: Eli Lilly and Company, Abbvie, Pfizer, Novartis, Roche, Janssen